Ets-1 is a transcriptional mediator of oncogenic nitric oxide signaling in estrogen receptor-negative breast cancer - Christopher Switzer; Robert Y.S. Cheng; Lisa A. Ridnour; Sharon A. Glynn; Stefan Ambs; David A. Wink (2012)
The Ets-1 transcription factor is a candidate breast cancer oncogene that regulates the expression of genes involved in tumor progression and metastasis. Ets-1 signaling has also been linked to the development of a basal-like breast cancer phenotype. We recently described a nitric oxide (NO)-induced gene signature that is associated with poor disease outcome in estrogen receptor-negative (ER-) breast cancer and contains both stem cell-like and basal-like components. Thus, we examined the role of Ets-1 in NO signaling and NO-induced phenotypes in ER- human breast cancer cells.Promoter region analyses were performed on genes upregulated in inducible nitric oxide synthase (NOS2) high expressing tumors for Ets-binding sites. In vitro mechanisms were examined in human basal-like breast cancer cells lines. NO signaling effects were studied using either forced NOS2 expression or the use of a chemical NO-donor, diethlylenetriamine NONOate (DETANO).Promoter region analysis of genes that are up-regulated in human ER-negative breast tumors with high NOS2 expression revealed that the Ets-binding sequence is the only common promoter element present in all of these genes, indicating that Ets-1 is the key transcriptional factor down-stream of oncogenic NOS2-signaling. Accordingly, both forced NOS2 over-expression and exposure to NO-donors resulted in significant Ets-1 transcriptional activation in ER- breast cancer cells. Functional studies showed that NO activated Ets-1 transcriptional activity via a Ras/MEK/ERK signaling pathway by a mechanism that involved Ras S-nitrosylation. RNA knock-down of Ets-1 suppressed NO-induced expression of selected basal-like breast cancer markers such as P-cadherin, S100A8, IL-8 and αβ-crystallin. Additionally, Ets-1 knock-down reduced NO-mediated cellular proliferation, matrix metalloproteinase and cathepsin B activities, as well as matrigel invasion.These data show that Ets-1 is a key transcriptional mediator of oncogenic NO signaling that promotes the development of an aggressive disease phenotype in ER- breast cancer in an Ets-1 and Ras-dependent manner, providing novel clues of how NOS2 expression in human breast tumors is functionally linked to poor patient survival.